Mechanical Properties of the Vertical Joints of Prefabricated Underground Silo Steel Plate Concrete Wall - Jun Chuai; Zhilong Hou; Zhenqing Wang; Lumin Wang (Advances in Civil Engineering)
Reliable joint connection is key to designing prefabricated structures. To study the mechanical properties of the vertical joints in the designed prefabricated underground silo steel plate concrete composite wall and verify their reliability, flexural and compressive experiments were conducted using two groups of six full-scale steel plate concrete composite wall specimens; the mechanical properties between jointed and jointless specimens were compared and analyzed. The experimental results indicate that all specimens are in the elastic stage during the entire loading process; further, they exhibit large stiffness and high bearing capacity without damages. Thus, the designed vertical joints of the steel plate concrete composite wall provide a reliable connection that is safe and applicable. Further, the flexural and compressive properties of jointed and jointless specimens were found to be similar; the newly designed prefabricated underground silo steel plate concrete composite wall could be designed using the “equivalent principle” that the combined wall design calculation with the joint could be equivalent to that without the joint.